MODERN INNOVATIVE TECHNOLOGIES IN TEACHING PEDAGOGY FOR MEDICAL STUDENTS - Kadirova , Munira; Yigitalieva, Nozimakhon (SAMBHRAM XABARNOMASI, 2024)
Medical education is undergoing a profound transformation with the integration of modern innovative technologies into teaching pedagogy. This paper explores how these technologies enhance learning for medical students, focusing on key innovations such as simulation-based learning, virtual and augmented reality, artificial intelligence, and mobile learning platforms. We discuss their impacts on knowledge retention, clinical skills, and student engagement. Our findings indicate that technological integration improves both theoretical understanding and practical competence, preparing students more effectively for the dynamic healthcare environment.